Effects of low-temperature Si buffer thickness and SiGe oxidation on sensitivity of Si1−xGex nanowire. (1st June 2015) - Lai, Yi-Lung; Chang, Tai-Yuan; Chang, Kow-Ming; Chen, Chu-Feng; Lai, Chiung-Hui; Chen, Yi-Ming; Whang, Allen Jong-Woei; Lai, Hui-Lung; Chen, Huai-Yi; Wang, Shiu-Yu
Abstract: Si1− x Ge x nanowire biosensors are attractive for their high sensitivity due to the large surface-to-volume ratio, high carrier mobility, and silicon compatibility. In this work, we study the effect of the thickness of the low-temperature Si (LT-Si) buffer layer on an insulator on the sensitivity of oxidized Si1− x Ge x nanowire samples with different Ge contents by increasing the Si buffer thickness from 20 to 60 nm. 3-Aminopropyltrimethoxysilane (APTMS) was used as a biochemical reagent. It was demonstrated that, with the proper Ge content and LT-Si buffer thickness, the sensitivity of the Si1− x Ge x nanowire is high and it can be further improved by Si1− x Ge x oxidation. This can be attributed to the reduction of the diameter to the nanometer order, which gives rise to an increased surface-to-volume ratio and further enhances the sensitivity of the biosensor.